2022
DOI: 10.3390/antibiotics11020238
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens and Antibiotic Susceptibilities of Global Bacterial Keratitis: A Meta-Analysis

Abstract: Bacterial keratitis (BK) is the most common type of infectious keratitis. The spectrum of pathogenic bacteria and their susceptibility to antibiotics varied with the different regions. A meta-analysis was conducted to review the global culture rate, distribution, current trends, and drug susceptibility of isolates from BK over the past 20 years (2000–2020). Four databases were searched, and published date was limited between 2000 and 2020. Main key words were “bacterial keratitis”, “culture results” and “drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 61 publications
(74 reference statements)
5
15
0
Order By: Relevance
“…Our study indicated that gram-negative bacteria preserve better susceptibility to the tested antibiotics compared with gram-positive bacteria, supporting evidence from previous reports [16,36,41,44,45,49]. The susceptibility of gram-negative bacteria to tested antibiotics seemed stable and maintained 90% over 15 years [7,16,19,41,45]. Most gram-negative isolates were susceptible to fluoroquinolone (96.3%) and cephalosporin (95.8%), followed by aminoglycoside (92.5%) in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study indicated that gram-negative bacteria preserve better susceptibility to the tested antibiotics compared with gram-positive bacteria, supporting evidence from previous reports [16,36,41,44,45,49]. The susceptibility of gram-negative bacteria to tested antibiotics seemed stable and maintained 90% over 15 years [7,16,19,41,45]. Most gram-negative isolates were susceptible to fluoroquinolone (96.3%) and cephalosporin (95.8%), followed by aminoglycoside (92.5%) in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The development of antimicrobial resistance is multifactorial, including injudicious use of antimicrobial agents, genetic mutational resistance and horizontal gene transfer of microorganisms per se [53]. Several recent studies have demonstrated the emergence of antibiotic resistance in ocular infections [16,19,41,42,45,49,50]. A certain proportion of antimicrobial-resistant bacteria among the isolated strains appeared annually in our study.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In a recent meta-analysis of 38 studies, the most common isolates worldwide were Staphylococcus spp (including Staphylococcus aureus and coagulase-negative Staphylococci) (41.4%, 95% confidence limits 36.2%-46.7%), Pseudomonas spp (17.0%, 13.9%-20.7%), Streptococcus spp (13.1%, 10.9%-15.7%), Corynebacterium spp (6.6%, 5.3%-8.3%) and Moraxella spp (4.1%, 3.1%-5.4%). 15 Streptococcus pneumoniae and Nocardia spp are more frequently reported in series from South India, [16][17][18] whereas in North Europe, Nocardia spp are rarely isolated (0.01%). [19][20][21] The introduction of new surgical procedures may modify the profile of isolates, for example, the outbreaks of keratitis from Mycobacterium chelonae (M. chelonae), M. fortuitum and M. abscessus associated with contamination of the surgical field with non-sterile water during laser refractive surgery.…”
Section: Bacteria Associated With Mkmentioning
confidence: 99%
“…Staphylococcus aureus ( S. aureus ) is a leading cause of bacterial keratitis, which is associated with severe inflammation, serious ocular damage, and permanent vision loss [ 70 ]. Clinically, the most effective treatment is broad-spectrum antibiotics.…”
Section: Role Of Spermidine In Ocular Diseasesmentioning
confidence: 99%